The Effect of Gambier Catechin Isolate on Cervical Cancer Cell Death (HeLa Cell Lines) - Rahmaddiansyah, Refa; Hasani, Suci; Zikrah, Azizah Amatu; Arisanty, Dessy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Cervical cancer is the second most common type of cancer in women worldwide. Human Papilloma Virus infection on the surface of the cervix is the most common cause which can cause abnormal growth of cervical cells. AIM: This research was conducted in vitro which aims to determine whether catechin compounds can inhibit the growth and regulation of cervical cancer cells (HeLa cell line). METHODS: This is experimental research using the colourimetric assay method and qualitative observation of cervical cancer cell morphology (HeLa cell line) under a fluorescence microscope. The administration of catechin compounds was tested at different concentrations to HeLa cells, namely 1000 g/ml, 500 g/ml, 250 g/ml, 125 g/ml, 62.5 g/ml, 31.25 g/ml. RESULTS: The smallest cell viability was obtained from a concentration of 1000 g/ml which was 5.98% while the largest cell viability was found at a concentration of 31.25 g/ml, which was 40.01%. The resulting IC50 value was 22.91 g/ml. Gambier catechin compounds have very high antioxidants because they contain an IC50 value < 50 g/ml. The effect of gambier catechin compounds on HeLa cell death can be found by increasing the percentage of dead cells. The difference in the fluorescence images of HeLa cells in the experimental group was assessed based on the percentage of the number of cells that died or underwent apoptosis, which was marked by a red or orange fluorescent image. At the concentration of IC25, 31.87% of dead cells were found, the concentration of IC50 was 51.09% of dead cells, and the concentration of IC75 was 82.51% of dead cells. The test results showed that there was a significant difference in the average percentage of cells undergoing apoptosis in all study groups with p <0.05. CONCLUSION: Based on research, it can be concluded that catechin compounds could inhibit the growth and regulation of cervical cancer cells (HeLa cell line). Later, it has the potential to be developed as an anticancer candidate for cervical cancer. Keyword: Cervical cancer, Catechin, Apoptosis, HeLa cell line, Cell death.